Do toe blood pressures predict healing after minor lower limb amputation in people with diabetes? A systematic review and meta-analysis. (June 2020) - Linton, Clare; Searle, Angela; Hawke, Fiona; Tehan, Peta Ellen; Sebastian, Mathew; Chuter, Vivienne
Purpose of study: To investigate toe systolic blood pressure and/or toe-brachial pressure index in predicting healing post minor diabetic foot amputations. Key methods: A systematic search of EMBASE and PubMed (including Medline and The Cochrane Library) was conducted from database inception to 9 March 2020. Two authors independently reviewed and selected relevant studies. Quality was assessed with a modified Critical Appraisal Skill Programme checklist. Main results: Ten studies met the inclusion criteria. Nine studies investigating toe systolic blood pressure reported healing occurred at mean toe systolic blood pressure values ⩾30 mmHg, ranging between 30 and 83.6 mmHg. The meta-analysis (four studies) found toe systolic blood pressure <30 mmHg had 2.09 times the relative risk of non-healing post amputation, compared to toe systolic blood pressure ⩾30 mmHg (relative risk = 2.09, 95% confidence interval: 1.37–3.20, p = 0.001). Two studies investigating toe-brachial pressure index report successful healing where toe-brachial pressure index >0.2, with one study reporting a higher value of 0.8. Main conclusions: Successful post-amputation healing outcomes were reported at mean toe systolic blood pressure ⩾30 mmHg, and the results varied considerably between the studies. Further research should identify whether variables, including amputation level, method of wound closure and length of post-operative follow-up periods, affect the values of toe systolic blood pressure and toe-brachial pressure index observed in this review.